Minat Siswa Tunarungu Dalam Mengikuti Pembelajaran Bulutangkis di Sekolah Menengah Pertama Luar Biasa - Areslon Lumban Gaol; Citra Resita; Febi Kurniawan (Universitas Singaperbangsa, 2021)
The government explains further in Law of the Republic of Indonesia no. 3 of 2005 concerning the National Sports System, that the guidance and development of sports for people with disabilities is carried out in the scope of educational sports, recreational sports, and achievement sports based on special types of sports for persons with disabilities that are in accordance with the condition of a person's physical and or mental disorders. In accordance with the explanation of the law above, people with special needs have the same rights to get education and develop their potential. Sampling in this study used a proportional random sampling technique, that is, a balanced number of samples were taken from each class. This type of research is a quantitative research, using a survey method with the research location. The research data is collected directly through: (1) observation, (2) interviews, and (3) document collection. The form of data analysis in this research is descriptive analysis. The results of this study show that the interest of deaf students in learning badminton is in the